Portrait painting expert answers to the questions every artist asks - Reichert, Tricia (Hauppauge, New York Barron's, 2013)
Portrait Painting covers a wide array of topics, including: Character, proportion, and angles, Creating effects through color and texture, Exploring different styles, Animal portraiture ... and much more
Proportions, character and likeness -- Light and shadow -- Backgrounds and composition -- Skin tones and color mixing -- Facial features and hair -- Clothing and hats -- Drawing and sketching -- Oil and acrylic -- Pastel, watercolor and gouache -- Exploring styles
"A Quantum Book"--Title page verso
Includes index
1
Keywords: Portrait painting -- Technique; Portrait painting -- Technique